1967
DOI: 10.1073/pnas.58.2.592
|View full text |Cite
|
Sign up to set email alerts
|

Normal mammalian muscle differentiation and gene control of isocitrate dehydrogenase synthesis.

Abstract: A new kind of laboratory mammal, the allophenic mouse, has been described by MinltZ.1' 2 These animals are artificial creations, since they are formed by aggregating cleavage-stage blastomeres in vitro from embryos of different genotypes, and the composites are then transferred to an "incubator" mother for further development. Despite their strange history, hundreds of such mosaic embryos have gone oIl to become healthy and long-lived adults. The mice are called allophenic because they display an orderly arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

1977
1977
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(51 citation statements)
references
References 20 publications
1
49
1
Order By: Relevance
“…Both in vitro (25) and in vivo (26, 28) experiments using ES cells and/or BM-derived stem cells showed that cell fusion is responsible for a certain percentage of phenotypic changes observed following stem cell transplantation. Cell fusion occurs in normal mammalian development during the formation of osteoclasts (36) and myoblasts (37) or during tumor progression (38). Recent in vivo studies suggest that hepatocytes derived from cell fusion of HSCs and host hepatocytes can correct underlying metabolic disorders and that fused cells can undergo reduction division (26).…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro (25) and in vivo (26, 28) experiments using ES cells and/or BM-derived stem cells showed that cell fusion is responsible for a certain percentage of phenotypic changes observed following stem cell transplantation. Cell fusion occurs in normal mammalian development during the formation of osteoclasts (36) and myoblasts (37) or during tumor progression (38). Recent in vivo studies suggest that hepatocytes derived from cell fusion of HSCs and host hepatocytes can correct underlying metabolic disorders and that fused cells can undergo reduction division (26).…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Cell fusion occurs during normal mammalian development. 51,52 In adult mammals, cell fusion may be associated with chromosomal abnormalities that can lead to oncogenic transformations. 53 Thus, it is crucial…”
Section: Discussionmentioning
confidence: 99%
“…1A). Myofibres are multinucleated, often containing hundreds of myonuclei, and are formed by the fusion of many myoblasts during embryonic and foetal development (Mintz and Baker, 1967).…”
Section: Introductionmentioning
confidence: 99%